2022
DOI: 10.37284/eajhs.5.1.582
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance, Knowledge and Attitudes toward COVID-19 Vaccines: A Cross-Sectional Study from Jigawa State, Nigeria

Abstract: Vaccination is one of the strategies to contain a pandemic such as coronavirus disease 2019. Nigeria with the highest number of people in Africa has fully vaccinated only 3.69% of its citizens as of February 2022. This study aims to assess the level of Covid-19 vaccine acceptance. A cross-sectional survey was carried out by adopting a systematic random sampling sum of 220 primary school teachers in Dutse municipal (the capital of Jigawa state, Nigeria). Data was gathered between August 2021 and September 2021 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Given historical boycotts of immunization programs in Northern Nigeria [ 43 ], and widespread rumours and misinformation about COVID-19 vaccines, we anticipated lower willingness to receive the COVID-19 vaccine [ 44 ]. Another study conducted between August and September 2021, just after our survey, reported that acceptance of the COVID-19 vaccine in Jigawa state was low, with 75% not believing in the safety of the vaccines, but that >60% would be willing to take the vaccine if it doesn’t harm those who have received it [ 45 ]. As of August 2023, just 35.6% of Nigerians had been fully immunized, far behind the WHO’s 70% vaccination coverage target by June 2022 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given historical boycotts of immunization programs in Northern Nigeria [ 43 ], and widespread rumours and misinformation about COVID-19 vaccines, we anticipated lower willingness to receive the COVID-19 vaccine [ 44 ]. Another study conducted between August and September 2021, just after our survey, reported that acceptance of the COVID-19 vaccine in Jigawa state was low, with 75% not believing in the safety of the vaccines, but that >60% would be willing to take the vaccine if it doesn’t harm those who have received it [ 45 ]. As of August 2023, just 35.6% of Nigerians had been fully immunized, far behind the WHO’s 70% vaccination coverage target by June 2022 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A research tool was designed after an extensive literature review [32][33][34][35]. This was customized and modified according to the aim and objectives of the study.…”
Section: Study Toolmentioning
confidence: 99%